Frontiers of distance learning in business education - Estelami, Hooman (Cambridge Scholars Press, 2013)
Distance education and online learning are interchangeable terms used to describe the delivery of educational content, whereby the student and the instructor are separated by geography, time, or both. Within the domain of business education, approximately one-third of all business schools offer online business programs, and many more are expected to follow in this direction. Considerable attention is therefore being given by business educators to the refinement of pedagogical approaches in th ...